2015
DOI: 10.1016/j.ejphar.2015.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional effects of dexmedetomidine on human platelet functions in vitro

Abstract: Platelets express the imidazoline (I)-receptor, I1 and I2, as well as the α2-adrenoceptor. Although dexmedetomidine, a selective α2-adrenoceptor agonist with some affinity for the I-receptor is expected to affect platelet function, the effects of dexmedetomidine on platelet functions remain unclear. In the present study, we investigated the effects of dexmedetomidine on human platelet functions in vitro. The effects of dexmedetomidine on platelet aggregation were examined using aggregometers. The formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…In contrast to the results of the present study, Kawamoto et al 4 reported in a previous study that dexmedetomidine enhances platelet aggregation measured using light transmission aggregometry with platelet rich plasma. The possible reasons for the discordance with our results might be methodological differences.…”
Section: To the Editorcontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the results of the present study, Kawamoto et al 4 reported in a previous study that dexmedetomidine enhances platelet aggregation measured using light transmission aggregometry with platelet rich plasma. The possible reasons for the discordance with our results might be methodological differences.…”
Section: To the Editorcontrasting
confidence: 99%
“…3 A recent study reported that high doses of dexmedetomidine induce adenosine diphosphate (ADP)-triggered platelet aggregation via alpha 2 -adrenoceptors in platelet-rich plasma. 4 Because high platelet reactivity to ADP and high thrombininduced clot strength measured using thromboelastography (TEG) are well-known risk factors for ischemic events in patients undergoing percutaneous coronary intervention, 5 the effect of dexmedetomidine on platelet aggregation and clot formation could be a pivotal issue. Based on the results of a previous study, 4 the authors hypothesized that dexmedetomidine could induce platelet aggregation and clot formation in whole blood and platelet-rich plasma.…”
Section: To the Editormentioning
confidence: 99%
“…As expected, ADP decreased cAMP level compared with control (4 (3-15) vs. 114 (81-128) pmol/10 9 platelets) and ticagrelor-inhibited ADP-induced suppression of intracellular cAMP (131 (97-150) vs. 4 (3-15) pmol/10 9 platelets, Figure 4A). Combining ADP and either epinephrine, norepinephrine, or brimonidine in the presence of ticagrelor fully restored suppression of intracellular cAMP production, achieving the same level as obtained with ADP alone in the absence of ticagrelor (16 (9-17), 20 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), or 23 (17-24) pmol/10 9 platelets, respectively). Adding dexmedetomidine induced a moderate reduction in cAMP concentration compared with the combination of ADP and ticagrelor (61 (53-67) vs. 131 (97-150) pmol/10 9 platelets) whereas clonidine had only a faint effect (102 (88-104) vs. 131 (97-150) pmol/10 9 platelets).…”
Section: Norepinephrine and Brimonidine Fully Inhibit Pge1-stimulatedmentioning
confidence: 61%
“…Since I 1 -receptor stimulation induces guanylate cyclase activation and the subsequent increase in the intracellular cGMP level, dexmedetomidine and clonidine can also participate in platelet aggregation inhibition [17]. Consequently, dexmedetomidine and clonidine have both enhancing and suppressive effects on platelet functions through their opposite action on α 2 -adrenoceptors and on I 1 -imidazoline receptors, respectively [18]. In our experimental conditions, these two antagonist mechanisms resulted in potentiation of ADP-induced platelet aggregation insufficient to induce platelet aggregation in the presence of ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, information on the effects of perioperative drugs, including anesthetics, on platelet function is important for patient care. We have described the effects on platelets of various anesthetics used during the perioperative period [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], but the effects on human platelets of many drugs used perioperatively remain to be clarified. Rocuronium ((+)-(17β-acetoxy-3α-hydroxy-2β-morpholino-5α-androstan-16β-yl)-1-allyl-1-pyrrolidinium bromide), an aminosteroid nondepolarizing neuromuscular blocker, is widely used for anesthesia and intensive care [ 8 ], but its effect on human platelet functions has not been examined.…”
Section: Introductionmentioning
confidence: 99%